Tukang timbal membina perahu: Tradisi dan inovasi - Pisol Maidin, (Universiti Kebangsaan Malaysia, 2003)
Tukang timbal are experienced and skilful boat builders. They design and supervise the process of boat construction from beginning to end. Their products tend to be greatly traditional in character and motives due largely to the inherited methods that they apply. This article, based on an in-situ observation and on interviews with boat-builders in Terengganu, studies the institution of boat-building by covering the way Malay boat-builders acquire knowledge, polish skills, organize their work, and the differences they show in their work. We note that they tend to improve and innovate, despite the fact that they follow closely what was done in the past